2017
DOI: 10.1111/1556-4029.13665
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Bridging: A Meta‐Analysis of Prevalence

Abstract: The main objective of this article was to analyze prevalence data about myocardial bridging (MB) in published studies. To this purpose, we performed a meta-analysis of studies published in English literature that contained data about the prevalence of MB and its anatomical characteristics. The overall prevalence was 19% (CI: 17-21%); autopsy studies revealed an overall prevalence of 42% (CI: 30-55%), CT studies 22% (CI: 18-25%), and coronary angiography 6% (CI: 5-8%). Most bridges were located on the left ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 132 publications
1
46
1
11
Order By: Relevance
“…Using coronary angiography, they are detected in as little as 0.4-12% (23)(24)(25)(26). Using dissection method, myocardial bridges are detected in a significantly larger number, so that the frequency of 53.3% determined in this paper coincides with the results of other authors using the same method and reported a frequency of 34.5% (27), 54% (28), 56% (29) and 58% (30).…”
Section: Discussionsupporting
confidence: 90%
“…Using coronary angiography, they are detected in as little as 0.4-12% (23)(24)(25)(26). Using dissection method, myocardial bridges are detected in a significantly larger number, so that the frequency of 53.3% determined in this paper coincides with the results of other authors using the same method and reported a frequency of 34.5% (27), 54% (28), 56% (29) and 58% (30).…”
Section: Discussionsupporting
confidence: 90%
“…The ventral merger of the atria represents the clearest case for a feature that is not shared by all birds, and that may occur only within Passeriformes and Psittaciformes. This feature has not been described previously to the best of our knowledge, and is different from the myocardial bridges that embrace coronary vessels in mammals (Polá cek, 1961;Van Nie & Vincent, 1989;Lee & Chen, 2015;Hostiuc, Negoi, Rusu, & Hostiuc, 2018). Given that the ventral merger was found in five out of five hearts of the Blackbird, it seems likely that it is a stable feature within a species even though it may exhibit much variation between species.…”
Section: Variation Between Bird Heartsmentioning
confidence: 68%
“…Myocardial bridging (MB) is a congenital abnormality characterized by the presence of an intramural course of a coronary artery that can give rise to systolic flow disturbances. According to a recent published meta-analysis the overall prevalence of MB was 19%, in autopsy studies 42%, in CT studies 22% and coronary angiography studies 6% 37 . The authors concluded that autopsy studies are the gold standard in evaluating the prevalence of MB and that high-resolution CT scanning of coronary arteries should be preferred over coronary angiography studies.…”
Section: Myocardial Bridgingmentioning
confidence: 99%